Tinjauan Hukum terhadap Kewenangan Brimob dalam Penggunaan Kekuatan pada Penanganan Demonstrasi Anarkis - Khalid, Muhammad; Fathinudin, Muhammad (HUMANIORUM, 2024)
This study examines the authority of the Indonesian Mobile Brigade (Brimob) in the use of force during the handling of anarchistic demonstrations, focusing on the legal regulations and their application in practice. The research highlights the legal frameworks established by Indonesian laws and police regulations to ensure proportionality in the use of force. The methodology employs a qualitative approach with a normative legal analysis, utilizing primary and secondary data sources such as laws, regulations, and judicial decisions. The findings indicate that Brimob's use of force is regulated by specific guidelines, including the principle of legality, necessity, and proportionality, although in practice, there are instances of excessive force leading to concerns regarding human rights compliance. The study concludes that while the regulations provide clear guidelines, better oversight and accountability are needed to ensure their proper implementation and adherence to human rights standards.